Arguments against the Textualization Regime: A Reply to Vincent L. Wimbush - Koch, Anne (What is religion?, 2021)
In this chapter Anne Koch and Vincent L. Wimbush debate the role of scripture in the study of religion and using this term as a key phrase in attempting to define it. In his initial definition, Wimbish argues that “ ‘[s]cripturalization’ . . . best captures the larger psychosocial, political-economic, and metadiscursive regime - shaping and shaped by nation-states - by which all are scripturally managed.” Koch responds with the claim that it is too narrow a definition and that we need to go even further; she suggests the use of “[s]emiotics - including grammar, meaning generation, time constructions, the way signs relate to objects, evaluations of repetition - and narratives (including excerpts from narratives as well as entire stories)” as “highly powerful structures in societies.”